2017
DOI: 10.1021/acsomega.7b01331
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and Composition-Dependent DNA Condensation by Thermosensitive Block Copolymers

Abstract: Successful intracellular delivery of genes requires an efficient carrier, as genes by themselves cannot diffuse across cell membranes. Because of the toxicity and immunogenicity of viral vectors, nonviral vectors are gaining tremendous interest in research. In this work, we have investigated the temperature-dependent DNA condensation efficiency of various compositions of a thermosensitive block copolymer viz., poly(N-isopropylacrylamide)-b-poly(2-(diethylamino)ethyl methacrylate) (PNIPA-b-PDMAEMA). Three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…The cationic block includes many of the synthetic cationic polymers discussed in the previous section. Some common examples include PLL, ,, PDMAEMA, , and poly­(vinyl benzyl trimethyl­ammonium chloride) (PVBTMAC). , The neutral block can be either hydrophobic or hydrophilic. Poly­(ethylene glycol) (PEG) is the most commonly employed hydrophilic neutral block. ,, For ease of block copolymer synthesis, poly­(oligo­(ethylene glycol) methyl ether methacrylate) (POEGMA) is also used .…”
Section: Complexation Of Nucleic Acids With Block Catiomersmentioning
confidence: 99%
See 1 more Smart Citation
“…The cationic block includes many of the synthetic cationic polymers discussed in the previous section. Some common examples include PLL, ,, PDMAEMA, , and poly­(vinyl benzyl trimethyl­ammonium chloride) (PVBTMAC). , The neutral block can be either hydrophobic or hydrophilic. Poly­(ethylene glycol) (PEG) is the most commonly employed hydrophilic neutral block. ,, For ease of block copolymer synthesis, poly­(oligo­(ethylene glycol) methyl ether methacrylate) (POEGMA) is also used .…”
Section: Complexation Of Nucleic Acids With Block Catiomersmentioning
confidence: 99%
“…The cationic block includes many of the synthetic cationic polymers discussed in the previous section. Some common examples include PLL, 36,37,118 PDMAEMA, 44,119 and poly(vinyl benzyl trimethylammonium chloride) (PVBTMAC). 9,38 The neutral block can be either hydrophobic or hydrophilic.…”
Section: Complexation Of Nucleic Acids With Blockmentioning
confidence: 99%
“…Steady-state as well as time-resolved fluorescence spectral studies to evaluate the DNA binding ability of different cationic DNA carriers are usually done using the EB dye. ,, However, because of the limited ability of EB to augment fluorescence intensity on binding with DNA, all these fluorescence studies using EB were carried out at very high concentrations of DNA. For example, Dey et al showed that the fluorescence intensity of EB increased only around 10 times from free EB to EB–DNA complexes using the concentration of calf thymus DNA at 25 μM (in terms of phosphate groups present in the DNA backbone) and the ratio of the concentrations of EB and the nucleotide was maintained as 1:15.…”
Section: Resultsmentioning
confidence: 99%
“…Steady-state fluorescence spectroscopy of DNA-intercalating dyes such as ethidium bromide (EB) is extensively carried out in dye displacement assays to probe the DNA-binding ability of various gene carriers. Nevertheless, this approach cannot be considered suitable for estimating the binding capability of gene carriers with DNA quantitatively because of overlapping and broad spectra of excluded and DNA-intercalated dyes as well as the conformational change of DNA in polyplexes. , This is why there arises a necessity for developing new techniques to study polyplex formation at various N/P ratios where maximum DNA condensation or gene transfection capability is exhibited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation